Construction and economic growth in developing countries of Africa : evidence from data of the last thirty years - Lopes, Jorge (2010)
The role of construction in economic growth and development has been addressed by various writers and international bodies, many of whom have focused in developing countries. The main aspect derived from a seminal work in this field (Bon, 1992) is that there is a changing development pattern of the construction industry based on the stage of development of a country’s economy. That is in the early stages of the economic development, the share of construction in gross domestic product (GDP) increases but ultimately decreases in industrially advanced countries. That finding was consistent with the classical approach in growth theory in which physical capital formation is the main engine of economic growth and development. Using most recent data spanning the last thirty years or so drawn from the United Nations (Yearbook of National Account Statistics: Main Aggregates and Detailed Tables) and World Bank publications (World Development Report and Africa Development Indicators), the results of the study corroborate, in the main, the assumptions of a previous work that posit that in the developing countries of Africa, the positive relationship between construction and the national economy concerns only a downturn economy, and an in an economic upward trend the pattern of the construction sector (measured as a share of value added in national output) tends to follow pari passu that of the rest of the economy.